THE INFLUENCE OF THE HORIZONTAL LOAD VIBRATIONS OF THE CRANE-PIPE LAYING MACHINE GIBBET ON THE LOAD MOMENT STABILITY - R. Yu. Sukharev; V. V. Tanskiy (Вестник СибАДИ, 2018)
Introduction: the main feature of operation of cranes-pipe layers is work in difficult ground conditions, which significantly affects the operating mode of  the machine. This factor is one of the main reason leading to the rocking of  the load on the crane-pipe laying machine gibbet and as a consequence it leads to emergency and contingency situations. In the research the forced  vibration of the load on the crane-pipe layer gibbet and the causes of their  occurrence and the problems to which they lead are observed. Engineering  solutions of predecessors are considered. A new approach to the solution of these problems is proved.Materials and methods: the design scheme of the crane-pipe laying machine is justified, assumptions are accepted, coordinate systems are  introduced, and a mathematical model of the crane-pipe-laying machine is compiled.Results: the following time dependences are constructed: the deflection of the cargo in the transverse plane of the crane-pipe layer  (horizontalvibrations), the deflection of the cargo in the longitudinal plane of  the pipe laying crane, the roll of the base machine, the change in the load  moment are also constructed. The influence of the horizontal vibrations of  the load on the change in the load moment and the occurrence of vertical vibrations is determined.Discussion and conclusion: the effect of horizontal vibrations on the change of the load moment is evaluated and as a consequence of the  negative effect on the stability of the crane-pipe laying machine is presented.